User acceptance of Immersive Virtual Reality (IVR) on information dissemination for nature tourism in Malaysia / Nurhafini Mohammad Nazri ... [et al.] - Mohammad Nazri, Nurhafini; Mokhsin, Mudiana; Abdul Razak, Fariza Hanis; Nordin, Nordiana; Mohd Som, Mohd Husni (Faculty of Information Management, 2022)
Immersive Virtual Reality (IVR) has the potential to alter the way people connect radically. This research aims to analyze user perspective on information dissemination of IVR displays for nature tourism and determine the significance of user acceptance of IVR applications in nature tourism applications. TAM model was used to evaluate user acceptance of IVR. Four constructs were used, which are Perceived Ease of Use (PEOU), Perceived Enjoyment (PENJ), Perceived Usefulness (PU), and Intention (I). The data was collected using a validated questionnaire and distributed through social media and face-to-face interaction.